K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 12 2016

\(\left(\frac{x}{2}\right)^2+\left(\frac{x}{3}\right)^2+\left(\frac{x}{4}\right)^2=\left(\frac{x}{5}\right)^2+\left(\frac{x}{6}\right)^2+\left(\frac{x}{7}\right)^2\)

\(\Leftrightarrow\frac{x^2}{2^2}+\frac{x^2}{3^2}+\frac{x^2}{4^2}=\frac{x^2}{5^2}+\frac{x^2}{6^2}+\frac{x^2}{7^2}\)

\(\Leftrightarrow\frac{x^2}{2^2}+\frac{x^2}{3^2}+\frac{x^2}{4^2}-\frac{x^2}{5^2}-\frac{x^2}{6^2}-\frac{x^2}{7^2}=0\)

\(\Leftrightarrow x^2\left(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}-\frac{1}{5^2}-\frac{1}{6^2}-\frac{1}{7^2}\right)=0\)

\(\Leftrightarrow x^2=0\). Do \(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}-\frac{1}{5^2}-\frac{1}{6^2}-\frac{1}{7^2}\ne0\)

\(\Leftrightarrow x=0\)

25 tháng 12 2016

thank you :)